Enhancement of Ozonation Reaction for Efficient Removal of Phenol from Wastewater Using a Packed Bubble Column Reactor - Saja Abdulhadi Alattar; Khalid Ajmi Sukkar; May Ali Alsaffar (Universitas Gadjah Mada, 2023)
In the ozonation process, the phenol degradation in wastewater undergoes a low mass transfer mechanism. In this study, ozonized packed bubble column reactor was designed and constructed to remove phenol. The reactor’s inner diameter and height were 150 and 8 cm, respectively. The packing height was kept constant at 1 m in accordance with the reactor hydrodynamics. The gas distributor was designed with 55 holes of 0.5 mm. The phenol removal efficiency was evaluated at ozone concentrations of 10, 15, and 20 mg/L, contact times of 15, 30, 45, 60, 75, 90, 105, and 120 min, and phenol concentrations of 3, 6, 9, 12, and 15 mg/L. The results indicated that the highest phenol removal efficiency of 100% was achieved at 30 min in presence of packing. Moreover, the use of packing improved the contact between the gas and liquid, which significantly enhanced the phenol degradation. Actually, a thin film over a packing surface enhances the mass transfer. Also, it was found that the phenol is degraded into CO2 and H2O through a series of reaction steps. Additionally, a kinetic study of a first-order reaction provided an efficient estimation of reaction parameters with a correlation factor of 0.997.